Understanding Nursing Care Omissions and Assessment Instruments in Emergency Departments: A Scoping Review Protocol - Provost, Josiane; Gosselin, Émilie; Rochefort, Christian (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2024)
Introduction: The omission of nursing care, characterized by the failure to perform necessary tasks due to various constraints (Kalisch et al., 2009), is a critical issue affecting healthcare globally (Aiken et al., 2018). This phenomenon is particularly pronounced in emergency departments (EDs), where high patient acuity and workload challenges often lead to lapses in care delivery.Objective: This scoping review aims to map the literature on nursing care omitted in EDs and the instruments used to measure the omission of nursing care in this setting.Method: We will follow Joanna Briggs Institute guidelines for scoping reviews and report according to PRISMA-ScR recommendations (Peters et al., 2020). Eligibility criteria include studies with nurses working in EDs, focusing on omitted nursing care, using a measurement instrument and adopting quantitative, qualitative, or mixed-methods designs.Discussion and Research Spin-offs: This review will provide an overview of nursing care omissions in EDs and the instruments used to measure them, thus shedding light on research needs and practical implications for improving care quality and patient safety.